Nursing Needs and Peculiarities of Patients With Apllied Artificial Ventilation of Lungs in Intensive Care Unit From the Perspective of Nurses - Matelionytė, Karolina; Daukšaitė, Laura (Slauga. Mokslas ir praktika, 2023)
Atificial pulmonary ventilation is prescribed in acute respiratory failure to help the patient ensure optimal blood circulation. Artificial lung ventilation is divided into invasive and non-invasive ventilation, and nurses must be able to ensure and maintain patients‘ vital functions. Research aim – analyze the nursing need of intensive care unit patients undergoing mechanical ventilation from the perspective of nurses. Research methods: analysis of scientific information sources, semi-structured interview, qualitative content analysis. Most important results and conclusions. After summarizing the answers received by the subjects, it was found that in order to secure the respiratory system in patients, it is necessary pump secretions from the intubation or tracheostomy tube, monitor the cuff pressure, as well as minitor the risk of leakage of the air stream of non-invasive masks, properly perform the hygiene of the central venous catheter, the hygiene of the eyes and whole body, to prevent bedsores, using auxiliary means. During study revealed that the specifics of nursing care are that patients with critical conditions are treated in the intensive care unit, requiring constant monitoring to minitor vital signs. Also has to perform a variety of nursing manipulations related to patient care, such as administering medications, regulating temperature, and meeting the needs of patients to eat and drink. The subjects distinguished that they must be able to prepare in time and quickly for complex procedures and to assist to the doctor.